Donor perspectives on strengthening capacity development for conservation. Issue 5 (25th September 2022) - Santy, Andrea; Loffeld, Thirza A.C.; Paterson, Stuart; Copsey, Jamieson A.; Bakarr, Mohamed I.; Rainer, Helga; Rehse, Eva; Bjorgvinsdottir, Steina; Scholfield, Katy; Kiragu Mwangi, Mike A.; Christen, Catherine A.
Abstract: Global perspectives on the pathways for developing capacity for conservation remain limited. Hindering the robustness of solutions is a dearth of opportunities to foster discussion and dialogue among capacity development practitioners, academics, partners, beneficiaries and donors. Additionally, little is known about donor perspectives on capacity development, and about pathways to developing a more sustainable investment in capacity development for conservation. The 2019 Capacity Building for Conservation Conference in London, UK, provided a unique opportunity to convene more than 150 capacity development practitioners from the global conservation community. The Conference included structured opportunities to hear donor perspectives on strengthening capacity development. Session leaders took detailed notes to document donor perspectives and the discussions around them. A thematic analysis of this empirical evidence resulted in the identification of four key themes with corresponding recommendations, consisting of (1) collaborative design of capacity development initiatives, (2) monitoring and evaluation, (3) longer-term and flexible investments, and (4) building strong relationships between donors and grantees. Given the Convention on Biological Diversity is currently drafting the long-term strategic framework for capacity development post-2020, and global calls to protect significant portions of our land- and seascapes, our recommendations are timely and may inform a way forward.